Effects of Drought Stress On Growth, Photosynthesis And Ultrstructure of Mesophyll Cell of Ulmus Szechuanica Fang Seedlings (Bangladesh Journal of Botany, 2022)
Effects of drought stress on growth, photosynthesis and ultrastructure of mesophyll cells of Ulmus szechuanica Fang seedlings were studied. Results showed that under drought stress both leaf water content (LWC) and relative water content (RWC) decreased significantly and height growth (GH) and base diameter growth (GD) declined. Pn, Tr, Gs, Ci and Ls were significantly affected by water deficit. With the continuing of drought, Pn decreased significantly, the change of Gs, Ci, Tr was same. There existed significant effects of drought on stomatal density (SD), stomatal length (SL), stomatal width (SW), individual stomatal area (As) and percentage of individual stomatal area (At) too. Under drought condition, change of structure and chloroplast morphology of the leaves was evident, the number of chloroplasts and orophil granules increased, their proportion in cells amplified. The number of starch granules became smaller, the arrangement of thylakoids among chloroplasts swollen and tend to be disordered.Bangladesh J. Bot. 51(3): 461-468, 2022 (September)